(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The National Action Plan for Climate Change (NAPCC)announced by the Hon. Prime Minister of India on June 30, 2008, envisagesseveral measures to address global warming. One of the important measuresidentified involves increasing the share of renewable energy in totalelectricity consumption in the country. NAPCC has set the target of 5%renewable energy purchase for FY 2009-10 against current level of around 3.5%.Further, NAPCC envisages that such target will increase by 1% for the next 10years, thus, NAPCC envisages renewable energy to constitute approximately 15%of the energy mix of India by the year 2020. This would require a quantum jumpin deployment of renewable energy across the country. Strong policy measuresand a proactive regulatory framework and innovative financing instruments wouldbe required, if the desired level of penetration of renewable energy is to beachieved. One such policy instrument prescribed in NAPCC is Renewable EnergyCertificate (REC) Mechanism, which would enable large number of stakeholders topurchase renewable energy in a cost effective manner.